2022
DOI: 10.3390/nano12193384
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of ZnONP Using Chamaecostus cuspidatus and Their Evolution of Anticancer Property in MCF-7 and A549 Cell Lines

Abstract: The ZnO nanoparticle synthesis using the leaf part of Chamaecostus cuspidatus was characterized using UV–Vis spectrophotometry, IR, XRD, DLS, FESEM, EDX, TEM, AFM and XPS. The MTT assay was used to examine the cytotoxicity activity against lung epithelial and breast cell lines, and the IC50 value was determined. The presence of ZnO nanoparticles, which range in size from 200 to 800 nm, was confirmed by the absorption peak at 350 nm. The median particle size was 145.1 nm, and the ζ -the potential was -19.45 mV,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…On the other hand, the phytochemicals that are present in the plant source are the ones that are thought to be responsible for the nanoparticles’ reduction and stabilization [ 14 , 46 ]. In agreement, we speculate in the present study that the phytochemicals, such as polyphenols, flavonoids, and carotenes found in the seed extract, might be deeply involved in the bio-reduction of the nanoparticles [ 42 , 43 ].…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…On the other hand, the phytochemicals that are present in the plant source are the ones that are thought to be responsible for the nanoparticles’ reduction and stabilization [ 14 , 46 ]. In agreement, we speculate in the present study that the phytochemicals, such as polyphenols, flavonoids, and carotenes found in the seed extract, might be deeply involved in the bio-reduction of the nanoparticles [ 42 , 43 ].…”
Section: Resultssupporting
confidence: 87%
“…Meanwhile, peaks were shown with 2θ values of 31.4°, 34.0°, 35.9°, 47.1°, 56.2°, 62.5° and 68.7° which corresponds to (100), (002), (101), (102), (110), (103) and (200) respectively. ZnO NPs synthesized from Andrographis paniculate, Chamaecostus cuspidatus and Agathosma betulina showed an identical XRD pattern [ 33 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations